2012
DOI: 10.1016/j.trstmh.2011.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatitis C virus infection among Egyptian healthcare workers in a national liver diseases referral centre

Abstract: Little is known about the prevalence of hepatitis C virus (HCV) among healthcare workers (HCW) in Egypt, where the highest worldwide prevalence of HCV exists. The prevalence of HCV, hepatitis B virus and Schistosoma mansoni antibodies was examined in 842 HCWs at the National Liver Institute in the Nile Delta, where >85% of patients are HCV antibody-positive. The mean age of HCWs was 31.5 years and they reported an average of 0.6±1.2 needlesticks/HCW/year. The prevalence of anti-HCV, hepatitis B surface antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 27 publications
1
43
2
Order By: Relevance
“…Forty-three (53.8%) participants were positive for S. mansoni antibodies with no significant difference between the HCV-RNA-negative and HCV-RNA-positive groups. A prevalence of S. mansoni of 36.4% in a number of Egyptian governorates has been reported (20), which is less than what we report here. Another study on health care workers at the National Liver Institute, Menoufia University (Egypt) reported an S. mansoni seroprevalence of 35.1% (21), which is also lower than our finding.…”
Section: Discussioncontrasting
confidence: 86%
“…Forty-three (53.8%) participants were positive for S. mansoni antibodies with no significant difference between the HCV-RNA-negative and HCV-RNA-positive groups. A prevalence of S. mansoni of 36.4% in a number of Egyptian governorates has been reported (20), which is less than what we report here. Another study on health care workers at the National Liver Institute, Menoufia University (Egypt) reported an S. mansoni seroprevalence of 35.1% (21), which is also lower than our finding.…”
Section: Discussioncontrasting
confidence: 86%
“…Munier et al reported that 48.8% of anti-HCV-positive HCWs were negative for HCV RNA and concluded that the cellular and innate immune responses to frequent occupational blood exposure might be associated with protection against HCV persistence in HCWs. [29] The rate of persistent HCV infection among our anti-HCV-positive HCWs was 81.6%. The frequency of HCV RNA positivity increased with age ( Table 3).…”
Section: Discusionmentioning
confidence: 80%
“…The kit uses HCV-specific primers and probes as well as internal controls. HBV surface antigen (HBsAg) (Murex) and anti-HBs (Adaltis, Italy) EIAs were performed according to the manufacturer's instructions and as previously described (2,35). Detection of Schistosoma mansonispecific IgG was performed by EIA according to the manufacturer's instructions (Novatec Immunodiagnostica GmbH, Germany).…”
Section: Methodsmentioning
confidence: 99%